Koroner arter baypas cerrahisinin nadir bir komplikasyonu: Çıkan aortta sakküler anevrizma - (:unkn) unknown (My University, 2010)
0
A rare complication of coronary artery bypass surgery: Saccular aneurysm
Keywords: Kalp ve Kalp Damar Sistemi